Context, Diversity and Engagement: Early Intervention with Australian Aboriginal Families in Urban and Remote Contexts - Robinson, G.; Tyler, W.; Jones, Y.; Silburn, S.; Zubrick, Stephen (Wiley-Blackwell, 2012)
This article describes challenges met implementing an early intervention programme for Aboriginal parents and their children in the NT (Northern Territory) of Australia in the context of efforts to remediate Aboriginal disadvantage. The intervention is an adaptation of an 8- to 10-week, manualised parenting programme designed for four- to six-year-old children with behavioural difficulties. It was implemented for both Aboriginal and non-Aboriginal children in urban Darwin and for Aboriginal children in three communities of the Tiwi Islands, near Darwin. Measured outcomes of the programme were positive overall with different outcomes by gender and Indigenous status. There were marked differences in retention of families from different socio-cultural backgrounds in the programme, with a significant loss of participants from referral through commencement to six-month follow-up. This drop-out was most marked for urban Aboriginal participants, despite highly flexible strategies of engagement and cultural adaptation of the approach pursued in each setting. The research provides lessons for the contextualisation of preventive interventions in diverse community settings and shows that systematic attention to cultural ‘fit’ of the intervention logic and cultural competence in engagement of disadvantaged families with multiple problems are fundamental to sustainability.